Ethnomedicinal Applications of Spices and Condiments in Nandurbar District (Maharashtra) - D. A. Patil2, S. K. Tayade1 *and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The present work is a result of ethnobotanical investigations among tribal and rural folks of Nandurbar district. The traditional knowledge of medicinal virtues of spices and condiments are still put into practice by the tribals such as Pawara,Bhil,Mavachi,Kokani, and Tadavi,apart from rural people. The paper focuses 26 angiosperm species belonging to 23 genera and 18 families of spices and condiments hitherto undocumented. They are used to combat about 27 human ailments prevalent in the area.Modern scientific examination is obviously needed to test their efficacy and veracity.<span style="line-height: 110%; font-family: ";Times New Roman";,";serif";; font-size: 10.5pt; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">